2008
DOI: 10.1111/j.1600-0625.2008.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of thymidine phosphorylase/platelet‐derived endothelial cell growth factor in basal cell carcinomas

Abstract: Thymidine phosphorylase (TP)/platelet-derived endothelial cell growth factor is associated with tumor angiogenesis. We evaluated the TP mRNA and protein expression in basal cell carcinomas (BCC) and in various skin tumors including numerous BCC histological simulants. Immunohistochemistry was performed on 99 paraffin sections of formalin-fixed skin tumors using monoclonal antibodies (mAb) against TP. TP mRNA levels were measured by real time RT-PCR in whole BCCs (wBCC) and laser capture microdissected (LCM) BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Paraffin‐embedded tissue sections (7 μm) were used for immunoperoxidase staining as previously described 20 . Primary antibodies were all purchased from Affiniti Research Products (Exeter, U.K.) and directed against 20S subunits pan‐α [monoclonal antibody (mAb) MCP231, 1 : 500], α6 (mAb MCP20, 1 : 500), β1 (= Y, mAb MCP421, 1 : 100), β2 (= Z, mAb MCP168, 1 : 100), β1i (mAb LMP2, 1 : 100), β5i (mAb LMP7, 1 : 100) and against the 19S subunit rpt5 [= S6a, polyclonal antibody (pAb), 1 : 500].…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin‐embedded tissue sections (7 μm) were used for immunoperoxidase staining as previously described 20 . Primary antibodies were all purchased from Affiniti Research Products (Exeter, U.K.) and directed against 20S subunits pan‐α [monoclonal antibody (mAb) MCP231, 1 : 500], α6 (mAb MCP20, 1 : 500), β1 (= Y, mAb MCP421, 1 : 100), β2 (= Z, mAb MCP168, 1 : 100), β1i (mAb LMP2, 1 : 100), β5i (mAb LMP7, 1 : 100) and against the 19S subunit rpt5 [= S6a, polyclonal antibody (pAb), 1 : 500].…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded skin biopsies sections were prepared and stained using a peroxidase-based protocol as previously described [17].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…LCM is normally used to demonstrate the presence of specific gene transcripts in cryosectioned tissues (Cristobal et al, 2004(Cristobal et al, , 2005. LCM of immunostained frozen tissue sections has been used successfully for gene expression analysis (Fend et al, 1999;Stoebner et al, 2008). We have also reported that gene expression of some antigen presenting cell-related molecules, such as HLA-DR a-chain, CD83, and CD86, can be analyzed in LCM-retrieved HLA-DR-expressing cells from immunostained frozen tissue sections (Kaneko et al, 2008).…”
Section: Discussionmentioning
confidence: 99%